Hydrometeorological Disasters in the Context of the Climate Crisis: A Regional Disaster Inventory Study in Türkiye - Mustafa Kemal Yaşar; Mahnaz Gümrükçüoğlu Yiğit (Doğal Afetler ve Çevre Dergisi, 2025)
The rapid growth of the global population, irregular urbanization and industrialization, present challenges to the sustainability of life and the world is currently facing an increasing prevalence of both natural and anthropogenic disasters. Climate change further exacerbates this situation by contributing to the rising frequency and intensity of hydrometeorological events. To effectively minimize the negative impacts of disasters, knowing assessing and analyzingtheir frequency, intensity, and consequences is essential. This necessitates the development of comprehensive disaster inventories. Such studies involve collecting and analyzing critical data to identify and manage potential disaster risks within specific regions. In this present study evaluates the long-term diversity of hydrometeorological disasters in the Sakarya, Kocaeli, and Istanbul provinces, situated in the Çatalca-Kocaeli section in the Marmara Region of Turkey. The study utilizes data from the General Directorate of Meteorology to analyze hydrometeorological disasters occurring from 1975 to 2020 across these provinces, with a focus on diversity, frequency, damages, and fatalities, evaluated on both an annual and seasonal basis. Damages are classified as light, moderate, or severe. This inventory is designed to offer valuable insights for researchers and policymakers aimed at mitigating loss of life and property damage. Additionally, it encompasses recommendations for disaster risk reduction strategies.